Isolated Demyelination of Corpus Callosum Following Hypoxia. Issue 1 (20th November 2018) - Marinelli, Lucio; Castelletti, Lara; Trompetto, Carlo
Corpus callosum includes a large amount of axons with various degrees of myelination, interconnecting cerebral hemispheres. Tumors, demyelinating diseases, infections, trauma and metabolic diseases as well as vascular lesions may affect corpus callosum, often extending to other white matter areas of the brain. We describe the case of a 76 years old male patient with history of arterial hypertension, diabetes mellitus and normal pressure hydrocephalus, developing dysphagia during hospitalization. Ab-ingestis pneumonia caused brain hypoxia and coma; brain magnetic resonance disclosed isolated demyelination of corpus callosum that was not present before hypoxia. Compared to neurons and astrocytes, oligodendrocytes are reported as particularly sensitive to hypoxia. Respiratory involvement without blood flow impairment could have lead to a prevalent oligodendrocytes damage, resulting in a selective demyelination of corpus callosum. Our patient indeed evolved into persistent vegetative state and died five months after hypoxic episode. This case report could give some insight about in vivo brain susceptibility to hypoxic damage.